Risks, Costs, and Benefits of Fluorocarbon Regulation - Bailey, Martin J. (American Economic Review, 2016)
and of alternative regulatory strategies. Fluorocarbons are widely believed to threaten the stratospheric ozone layer and to influence climate. In fact, all the pertinent effects are highly uncertain, and could well be entirely different from what currently popular hypotheses suggest. The eventual ozone-depleting effect of fluorocarbons has been reduced approximately to zero in recent trials of the going models of stratospheric chemistry, due to new experimental data on the pertinent chemical reactions. The climatic effects could imply either net benefits or costs. Subject to these wide uncertainties, the recent data revisions lead my assessment of benefits of costs to a net benefit expected from continued unregulated emissions of fluorocarbons, due mainly to energy-related benefits of climatic warming. That is, it suggests that regulation would do more harm than good. However, there is a nontrivial possibility of extreme damage, and we might wish to insure against this threat by restricting emissions. Analysis of the buildup of risk over time suggests that the optimum time for a decision on regulation will be ten years or so in the future. In the meanwhile, further research will have narrowed down the uncertainties. At present they are so wide that a wrong decision either way could be very costly to the U.S. economy. The worldwide character of the problem adds both to the uncertainties and to the